Research on Selection Parameters of Isolation-Support Dual-Purpose Piles Based on Orthogonal Tests - Yang Song; Songqi Li; Guochong Lou; Guang Hao; Siyu Meng; Chen Liu (Advances in Civil Engineering)
Placing isolation piles outside the foundation pit can not only control the deformation of the surrounding environment but also prevent the additional impact of extra-pit loads on the foundation pit support system. Relying on the deep foundation pit project of a subway station in Shijiazhuang, this article utilizes numerical methods to establish an orthogonal test calculation model from the above two perspectives. It conducts multifactor and multi-indicator range analysis and variance analysis for the isolation-support dual-purpose piles, as well as a significance test. Finally, the balance coefficient is defined to evaluate its corrective effect on the deformation of the foundation pit under asymmetrical loading. The sequential control rate and growth rate of railroad subgrade settlement are defined to evaluate the settlement control effect. The research results show that during the excavation stage of the main foundation pit, the pile length is the most significant factor influencing displacement control. The balance coefficient is close to 1.0 when the pile length reaches 21.8 m, leading to symmetrical equilibrium in the deformation of the retaining piles on both sides of the main foundation pit. The sequential control rate of railroad subgrade settlement is 32.78%, with the most effective control achieved under conditions of the same incremental pile length. At the stage of the secondary pit excavation, the equivalent bending stiffness is the most significant influencing factor of settlement control, and the growth rate of railroad subgrade settlement is 52.34% when the pile type is Φ1250@1500, so that the railroad subgrade settlement caused by secondary pit excavation has the smallest proportion in the total settlement. The research results can provide a reference for designing similar projects.